Changes in access to community health services among rural areas affected and unaffected by hospital closures between 2006 and 2018: A comparative interrupted time series study - Bell, Nathaniel; Hung, Peiyin; Merrell, Melinda A.; Crouch, Elizabeth; Eberth, Jan M. (The Journal of rural health, 2023)
Purpose Recent studies suggest that Federally Qualified Health Centers (FQHC) may be expanding their provision of primary care in rural communities that experience a hospital loss. Whether these trends are different from rural areas not being affected by rural hospital closures is unknown. Methods Data included Centers for Medicare and Medicaid Services Provider of Services files, the Cecil G. Sheps hospital closure database, and American Community Survey estimates. Changes in straight‐line distances to the nearest FQHC and rural health clinic (RHC) were compared between areas affected and unaffected by a rural hospital closure in a matched case control study design using an interrupted time series model. Findings There was no instantaneous percentage point increase in FQHC (2.41, 95% CI −0.79 to 5.60, P .140) or RHC (3.27, 95% CI −1.12 to 7.67, P .144) access following hospital closures compared to changes in access occurring in other rural areas. On average, rural ZIP codes affected by hospital closures exhibited a 0.84 percentage point increase in FQHC access over time (95% CI 0.40‐1.28, P .000), but similar trends were also found within unaffected ZIP codes classified as small rural areas. Conclusions Rural areas impacted by hospital closures did not experience an increase in proximity to FQHCs or RHCs relative to changes in access occurring in other rural areas. Over time, most rural areas are seeing an increase in access to FQHCs and RHCs. Policies are needed to incentivize primary care providers to target geographic areas experiencing a hospital closure.